2005
DOI: 10.2166/wst.2005.0529
|View full text |Cite
|
Sign up to set email alerts
|

Solving fecal coliform growth/reactivation in biosolids during full-scale post-digestion processes

Abstract: Fecal coliform recurrence has been observed at the City of Los Angeles Hyperion Treatment Plant during pilot-scale experiments with a designated thermophilic battery of six anaerobic digesters, while other digesters were still at a mesophilic temperature. Several lab and full-scale experiments indicated the following possible causes of the growth/reactivation of fecal coliforms in post-digestion: a) contamination of thermophilically digested biosolids with mesophilically digested biosolids; b) a large drop in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We opted for reducing the digester temperature in Phase V to the lower end of the thermophilic range, to maintain disinfecting conditions, while reducing odor emissions. In addition, the implementation of a final mesophilic stage would result in a relatively low postdigestion biosolids temperature, which could be a factor contributing to fecal coliform recurrence in postdigestion (Iranpour et al, 2003(Iranpour et al, , 2004c. The reduction of the temperature in Phase V would imply elimination of the possibility of operation under Alternative 1, as the time-temperature requirement for batch disinfection was not met.…”
Section: Discussionmentioning
confidence: 99%
“…We opted for reducing the digester temperature in Phase V to the lower end of the thermophilic range, to maintain disinfecting conditions, while reducing odor emissions. In addition, the implementation of a final mesophilic stage would result in a relatively low postdigestion biosolids temperature, which could be a factor contributing to fecal coliform recurrence in postdigestion (Iranpour et al, 2003(Iranpour et al, , 2004c. The reduction of the temperature in Phase V would imply elimination of the possibility of operation under Alternative 1, as the time-temperature requirement for batch disinfection was not met.…”
Section: Discussionmentioning
confidence: 99%
“…7.9 log g/DS reduction in 7 days (to undetectable levels, no increase observed after 14 days of storage) [23] Cow manure storage (untreated microcosms) 7 °C E. coli 0157:H7 declined slightly by 0.24 log g/ DS in a particular organism [23]. Therefore, the reducing storage temperatures identified by Sprigings and Le [22] and Iranpour et al [21] in biosolids storage are likely to lessen the stress on cell functions and limit excessive energy expenditure for indicator bacteria held within the sludge matrix. Consequently, the steady growth and prolonged survival of E. coli bacteria is likely in uncontrolled biosolids storage environments.…”
Section: Escherichia Coli Death Rate and Temperaturementioning
confidence: 84%
“…Post-digestion, the temperature of sludge will gradually reduce particularly after dewatering and during the biosolids storage phase which normally occurs in uncontrolled, open bays. The reoccurrence of faecal coliforms in post-digestion biosolids was attributed to this temperature reduction by Iranpour et al [21] and researchers argue that maintaining a minimum temperature of 50 °C (representative of the up-stream thermophilic digestion process) may prevent growth of faecal coliforms. Sprigings and Le [22] showed that biosolids retained a higher temperature after centrifuge dewatering for approximately 12 h, possibly an effect of residual heat from the digestion process.…”
Section: Escherichia Coli Death Rate and Temperaturementioning
confidence: 99%
“…Methanogens were found to consume the organic sulfur compounds and hence conditions that stimulated methane production resulted in lower odor production from organic sulfur compounds. Iranpour et al (2005a) investigated the effect of digester temperature changes in the thermophilic range on the production of volatile Acrylamide-based polymers were found to result in the generation trimethylamine during lime stabilization. Meckes and Smith (2005) argued that risk management techniques should be evaluated on how well they are able to demonstrate reduction of risks, the factors to consider include pathogens of concern in biosolids, the analytical techniques to identify and quantify microorganisms in biosolids, and the relationship between risk management and the measurement of fecal coliforms and pathogens in biosolids.…”
Section: Odor Issuesmentioning
confidence: 99%